Complementarities, costly investment and multiple equilibria in a one-sector endogenous growth model - Thompson, Maria João Ribeiro (2003)
In this paper we develop a multiple equilibria one-sector R&D-based growth model, in which the key aspects are the assumption of complementarities between capital goods in the production function and the assumption of costly investment in capital. This second assumption is new to the R&D-based literature. The equilibrium solutions are obtained when the Preferences curve, which mirrors consumers’ savings decisions, and the Technology curve, which represents equilibria on the production side, cross. The combination of the two key assumptions produces a non-linear Technology curve, which consequently crosses the Preferences curve more than once, thus generating multiple equilibria. A numerical solutions exercise obtains two equilibria. Application of the stability under learning criterion allows for the identification of the two equilibria as stable. Expectations can lead the economy to either the equilibrium characterised by high-growth and high-interest rates, or to the equilibrium characterised by low-growth and low-interest rates. Hence, with this model, we wish to contribute to endogenous growth literature by providing a mechanism to explain how an economy can experience multiple equilibria situations.